Theatres of migritude: towards a dramaturgy of African futures - Mwenya, Kabwe Beverly (Centre for Theatre Dance and Performance Studies, 2023)
The thesis aims to contribute to the genre of black migrant cultural production called migritude, developed largely in African diasporic literary circles and tracing its evolution from the Négritude movement. It will mobilize Shailja Patel's significant work to shape a new migritude that stands in continuation and in contestation with the older version of this artistic project. The research question at the heart of the thesis is, what does it mean to have a migrant attitude for theatre and performance making? The thesis explores an approach to thinking about how a relationship between migration and African futurism can be put towards a dramaturgical practice mobilized in the direction of possibility, potential and a more hopeful future. The quest undertaken here is to find out what alternative understandings of African migrancy exist in the spirit of the five case studies, namely Migritude by Shailja Patel, Every Year, Every Day I am Walking by Magnet Theatre, Moj of the Antartctic: An African Odyssey by Mojisola Adebayo, Afrogalactica Deep Space Scrolls by Kapwani Kiwanga and Astronautus Afrikanus, devised by a group of students at Rhodes University under my direction. By analysing each of these performance texts through a different lens, the thesis aims to develop a pliable dramaturgical framework for a migrant attitude which leverages some of the aesthetic features of migritude artistic work as noted by Vanita Reddy (2020). These include defining Africa by movement, linking the concept of migrant with the concept of colonial history and the diasporic refusal of return. Here a migrant attitude also includes Thomas Nail (2015) and Veejay Prashad's (2010) contentions that the migrant is central to a project of social re-imagining, as well as Mark Fleishman's (2015) notion of a dramaturgy of displacement where movement and migration form a core part of both the form and content of the work.